Salivary flowand oral complaints in adult dental patients - Bergdahl M (Blackwell Synergy, 2000)
Saliva plays an important role in maintaining oral health and functions. In the present study, unstimulated and stimulated whole salivary flow and various oral complaints were surveyed in 1427 individuals, 669 men (47%) and 758 women (53%). These individuals, aged 20 to 69 years and from different socioeconomic backgrounds, were recruited from 2000 randomly selected men and women in the register of the public dental health service in northern Sweden. The unstimulated salivary flow rate ranged from 0 to 2.07 mL/min (mean 0.33ºSD 0.26) for men, and from 0 to 1.35 mL/min (mean 0.26ºSD 0.21) for women. The stimulated salivary flow rate ranged from 0.17 to 7.3 mL/min (mean 2.50ºSD 1.06) for men, and from 0 to 6.40 mL/min (mean 2.02ºSD 0.93) for women.Women over 55 years of age had a reduced unstimulated salivary flow (P°0.05). Individuals with many teeth had a higher stimulated salivary flow than those with fewer teeth (P°0.001). Male smokers had a lower unstimulated salivary flow than male non-smokers (P°0.05).